THE EFFECT OF FOREIGN INVESTMENTS ON THE SUSTAINABLE DEVELOPMENT OF THE ECONOMY OF UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article examines the impact of foreign investments on the sustainable development of Uzbekistan's economy. The paper discusses the positive effects of foreign capital inflow into the country's economy, including job creation, increased product diversity, and enhanced international competitiveness. It also analyzes how foreign investments facilitate the introduction of modern technologies and management practices, and how this enhances the efficiency of various economic sectors.
Keywords: foreign investments, economic development, modern technologies, competitiveness, investment policy.